Sacrificing Quantity for Quality: Better Focusing Prosecutors' Scarce Resources - Bibas, Stephanos (2011)
This short essay responds to Adam Gershowitz’s and Laura Killinger’s article The State (Never) Rests: How Excessive Prosecutorial Caseloads Harm Criminal Defendants. The authors rightly argue that prosecutorial overwork harms justice in any number of ways: it delays cases, frustrates victims, makes it harder to spot and free innocent defendants, and impedes lowering punishments for sympathetic defendants. The root problem, however, is less about underfunding than about skewed priorities and metrics of success. Too often, prosecutors do not think strategically about using their discretion to proactively set priorities and focus on system-wide tradeoffs. Throwing money at the problem would only pour fuel on the fire, encouraging prosecutors to widen their nets in the inexhaustible sea of potential cases. A surer solution is to refocus on making the best use of limited money, to change from worshipping quantity to prizing quality. Prosecutors need to focus not just on what to do but also how to do it: fairly, respectfully, and effectively